On the relation between capital flows and the current account - Anne Oeking; Lina Zwick (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2015)
Imbalances in the current and financial account have been at the heart of the discussion on global imbalances. With respect to monitoring macroeconomic stability it is highly important to know whether capital flows cause reactions in the current account or whether they rather adjust to changes in the current account, and hence which variable can be used as an indicator for upcoming imbalances. In this paper, we study the dynamics of the current account and different types of net capital flows (portfolio flows, direct investment and other investment flows) for selected OECD countries applying the concept of Granger-causality. Moreover, in a non-linear model we test whether the direction of Granger-causality changes over the business cycle. Our results show that the current account generally Granger-causes the financial account components. However, for short-term flows the direction changes over the business cylce: they seem to finance the current account during economic downturns, while inducing its changes during upturns.
Keywords: F32; 330; Current Account; International Capital Flows; Granger-causality; Threshold VAR